Empirical estimation of REER trend for Ukraine - Artem Vdovychenko (Graduate Institute of International and Development Studies, 2021)
In this study, we apply BEER and FEER approaches to estimate the REER trend on Ukrainian data. By applying BEER we were able to identify the long-run factors which explain the dynamics of the REER trend. FEER approach gives us information on the determinants and measurements of the current account norm for Ukraine. Although the two approaches are different in their nature, both of them identify the periods of REER undervaluation in the first half of the 2000s, after the crises of 2008-2009 and 2014- 2015. Significant overvaluation was detected in the period 2011-2013. For more recent years estimates indicate moderate overvaluation of the REER which decreased in the second half of 2020.
Keywords: F31; F32; 330; BEER; FEER; REER trend; misalignment; current account norm; underlying current account